(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In order to overcome the shortcomings such as extended time and high cost of using solar cells to experiment, this paper successfully used a DC power supply and a variable resistor to simulate the solar cells output characteristic curves. Operating principles, equivalent circuits, and illustrative example in terms of computer simulation are presented in order to validate the approach. This paper deals the design of DC/DC converter which can make voltage maintained at a specified value. MATLAB simulation for Open–loop and Closed–loop controlled Buck converter for the solar cells is discussed and the results are presented.